Compliance of the application of the advanced vital support protocol in trauma patients Hospital Central Universitario Dr. Antonio María Pineda (Boletin Médico de Postgrado, 2022)
This study was performed to determine compliance of the application of the Advanced Trauma Vital Support Attention Protocol (ATLS) in polytrauma patients admitted to the Hospital Central Universitario Dr. Antonio María Pineda during the August-November 2019 period. In regards to the pre-hospital care, the majority of patients did not receive attention at the scene (95.3%), the time between the event and the initial attention was 15-60 minutes (68.7%), most of them were transferred in private vehicles (95.3%), without prior call to the hospital (99.6%) and due to lack of availability, first aid was not performed. The patients arrived less than an hour after the accident (65.7%), received immediate care (84.3%), the staff did not expect them (99.67%), did not have a multidisciplinary team (98.6%) nor a leader (96%), were received in most cases by first-year surgery residents (61.4% and 51.1%). There was availability of laryngoscope (97.6%) and orotracheal tube (62.9%), peripheral venous catheterization was performed (100%) and crystalloid solutions were administered (98.6%). In the primary review, with respect to the airway with cervical spine control, three parameters were fulfilled, in regards to the breathing and ventilation two parameters, circulation with bleeding control three parameters and neurological deficit one parameter. The complementary tests done were chest radiography (97%) and pelvis (88%). For the parameters of the secondary review, the staff diagnosed the type of injury (99.3%), four thorax parameters and three abdomen parameters were fulfilled; the rest of the parameters were not met. In the tertiary review, inadvertent limb injuries were identified (66.11%) and 5.65% of deaths were recorded.
Keywords: multiple trauma; emergency medical services; prehospital care; hospital care; emergencies